Loss of native brown trout diversity in streams of the continental Croatia - Kanjuh, Tamara; Marić, Ana; Škraba Jurlina, Dubravka; Simonović, Predrag; Špelić, Ivan; Piria, Marina; Maguire, Ivana (Frontiers in Environmental Science, 2024)
The genetic diversity of brown trout in the Western Balkans has been disrupted by the introduction of non-native Atlantic phylogenetic lineages and non-native haplotypes of the Danubian phylogenetic lineage. The Western Balkans is characterized by the greatest phenotypic and genotypic diversity of trout populations, and a large part of the internal territory belongs to the Black Sea basin, where the Danubian Da1 haplotype is native. Artificial propagation of allochthonous lineages in the Western Balkans has a long history, and these populations are often the only available material for stocking rivers attractive for fishing. Fifteen populations in the Danube basin of the continental Croatia were analysed. The analysis of eight microsatellite loci was performed to determine the structure of brown trout populations, as well as the degree of introgression of allochthonous genetic material into the autochthonous. The results of this study showed significant genetic similarity among brown trout populations, confirming a long history of introduction with non-native genetic material. The main reason was uncontrolled stocking with inadequate material, which is available in fish farms and consists mainly of brown trout of the Atlantic phylogenetic lineage. The results of this study also indicated stocking with brown trout of the non-native haplotypes of the Danubian phylogenetic lineage. The potential breeding origin of brown trout carrying the Danubian Da2 mtDNA haplotype and ways of its introduction into rivers have yet to be investigated. For the survival of the unique gene pool of brown trout in Croatian rivers, it is of fundamental importance to know the structure of wild and farmed populations with the aim of proposing and implementing conservation measures.